Perancangan Alat Penyaringan Ampas Tahu dengan Pendekatan Anthropometri - Ramadhan, Admiral; Satoto, Handy Febri (Fakultas Teknik UMRI, 2024)
To reduce time efficiency, the tofu dregs filtering tool uses a design that is adapted to the anthropometry of 3 Bu Rita Tofu Factory UKM employees in 3 measurement dimensions, namely Standing Elbow Height (TSB), Hand Reach (JT), and Hand Grip Diameter (DGT). The 3-dimensional anthropometric measurement data is adjusted to the 10th percentile which is in accordance with the tool dimension requirements to make operations easier for employees. After using a new tool to filter tofu dregs using human power, it can help employees at Mrs. Rita's tofu manufacturing factory UKM to be able to filter tofu dregs quickly and efficiently. The average time used before using the machine is 13 minutes 6 seconds. After using the dregs filtering tool, the time used was 8 minutes 4 seconds. The new tofu dregs filter system is equipped with stainless steel so that it can reduce fatigue and increase the time efficiency value by 60.15% greater than the old tofu dregs filter. The time period required for the process of making this tofu dregs filtering tool, including design, material selection, to completion, is 24 working days. The process of making a tofu dregs filter tool requires a tool production cost of Rp. 3,500,000.